2006
DOI: 10.1007/s11242-005-6088-1
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a fluid in a horizontal saturated porous layer: effect of non-linear concentration profile, initial, and boundary conditions

Abstract: Carbon dioxide injected into saline aquifers dissolves in the resident brines increasing their density, which might lead to convective mixing. Understanding the factors that drive convection in aquifers is important for assessing geological CO 2 storage sites. A hydrodynamic stability analysis is performed for non-linear, transient concentration fields in a saturated, homogenous, porous medium under various boundary conditions. The onset of convection is predicted using linear stability analysis based on the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 32 publications
4
125
0
Order By: Relevance
“…These onset time and wavenumber are in good agreement with those found in several previous theoretical studies [25][26][27][28][29][30][31] . Additionally, these onset characteristics are close to those evaluated experimentally in systems analogous to the CO 2 /water system 9,11 .…”
Section: Characteristics Of the Instabilitysupporting
confidence: 92%
“…These onset time and wavenumber are in good agreement with those found in several previous theoretical studies [25][26][27][28][29][30][31] . Additionally, these onset characteristics are close to those evaluated experimentally in systems analogous to the CO 2 /water system 9,11 .…”
Section: Characteristics Of the Instabilitysupporting
confidence: 92%
“…In particular, the early-stage development of this instability has been characterized both theoretically and experimentally for porous media or Hele-Shaw cells with a focus on the critical time and wavenumber for the onset of convection 5,[10][11][12]16,[18][19][20][21][22][23][24][25][26][27][28][29] . Studies have reported the impact on these properties of boundary conditions 21,22,28 , anisotropy of the permeability 16,[23][24][25]28 , geometry of the system 26 , compressibility and interface movement 27 , a geothermal gradient 28,29 , and control parameters in laboratory experiments 5,[10][11][12]19 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported the impact on these properties of boundary conditions 21,22,28 , anisotropy of the permeability 16,[23][24][25]28 , geometry of the system 26 , compressibility and interface movement 27 , a geothermal gradient 28,29 , and control parameters in laboratory experiments 5,[10][11][12]19 . However, an important aspect that has been less investigated is the impact of chemical reactions on such instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies of one-sided convective systems have focused on the conditions required for the onset of convection, which presents significant theoretical challenges because the diffusive base state is both time-dependent and nonlinear. Various theoretical studies (Hassanzadeh, Pooladi-Darvish & Keith 2006;Riaz et al 2006;Xu, Chen & Zhang 2006;Slim & Ramakrishnan 2010) have been complemented by direct numerical investigations (Riaz et al 2006;Hassanzadeh, Pooladi-Darvish & Keith 2007) and laboratory experiments (Fernandez et al 2002;Backhaus, Turitsyn & Ecke 2011;Slim et al 2013) that explore the onset of convection.…”
Section: Introductionmentioning
confidence: 99%